PRAGMATIC-LINGUISTIC FEATURES OF NEGATIVE EVALUATION IN NEUTRALLY EVALUATIVE WORDS - Umarova Zumradxon Avazxon qizi (Modern American Journals, 2025)
This article explores the pragmalinguistic mechanisms through which neutrally evaluative words acquire negative connotations in specific communicative contexts. Drawing on theoretical perspectives from semantics, pragmatics, and cognitive linguistics, the study demonstrates that evaluation is not an inherent or static feature of a word, but often shaped by speaker intent, contextual cues, and cultural norms. Through analysis of Uzbek, English, and Russian examples, the article reveals how neutral lexemes can undergo evaluative degradation, particularly under the influence of irony, presupposition, and negative contextual framing. The findings highlight the dynamic nature of linguistic evaluation and its dependence on interactional and sociolinguistic factors.